Pengaruh Edukasi Konsumsi Tablet Fe terhadap Kepatuhan Ibu Hamil dalam Mengkonsumsi Tablet Fe selama Kehamilan di Puskesmas Penerokan - Suratiyah, Suratiyah; Ariyani, Lusi; Hariyanti, Reni; Riya, Rosa; Radiah, Radiah (Jurnal Akademika Baiturrahim Jambi, 2026)
Anemia is a condition where red blood cells (RBCs) are insufficient to deliver oxygen to tissues. Because this is difficult to measure, anemia is defined as a low hemoglobin (Hb) concentration (normally >11 g/dL), a normal red blood cell count (RBC) of 3.42-4.55 x 1012/L, and a hematocrit (Hct) of >33 (Wibowo et al., 2021). To determine the effect of education on consuming iron tablets on pregnant women's compliance with iron tablet consumption. This study used a quantitative method with a pre-experimental approach with a pre-test-post-test group design, covering both before and after education. The population and sample size in this study consisted of 34 respondents. Data collection was conducted using a questionnaire. Data analysis used the Wilcoxon test. The univariate study found that 22 pregnant women (64.7%) were compliant with iron tablet consumption. 30 pregnant women (88.2%) were compliant with iron tablet consumption with family support. 27 pregnant women (79.4%) had a good visit. The results showed a p-value of 0.000 (p<0.05). There was an effect of iron tablet consumption education on pregnant women's compliance with iron tablet consumption during pregnancy at the Penerokan Community Health Center in 2025.